In vitro Propagation and Genetic Homogeneity Assessment of Dendrobium crepidatum Lindley & Paxton - Dhungana, Savita; Pradhan, Shreeti; Paudel, Mukti Ram; Pant, Bijaya (Plant Tissue Culture and Biotechnology, 2022)
In vitro propagation is one of the most dependable methods to develop true-to-type plants for the commercial and conservation aspects. This study aims to produce the genetically identical plantlets of Dendrobium crepidatum Lindley and Paxton using in vitrodeveloped shoot explants. Coconut water (5 - 10%) supplemented Murashige and Skoog (MS) medium responded towards effective shoot formation with BAP (1.0 - 2.0 mg/l) and NAA (0.1 - 0.5 mg/l). NAA (0.5 - 1.0 mg/l) alone or in combination with BAP was found to be effective for root initiation in MS medium. Four RAPD (Random Amplified Polymorphic DNA) primers viz., G04, G10, G17 and G18 showed 100% genetic homogeneity in plants obtained from in vitro-developed shoot explant. However, G10, G17 and G18 RAPD primers showed 60, 25 and 100% genetic polymorphisms respectively in plants obtained from callus. Plants obtained from callus were genetically polymorphic where somaclonal variation might occur. This study reported the successful genetic homogeneity of shoot explant-derived plants of D. crepidatum. Hence, the present study has validated the establishment of standard in vitro protocol for significant propagation of superior genetically indistinguishable D. crepidatum for viable conservation and commercialization. Plant Tissue Cult. & Biotech. 32(1): 1-11, 2022 (June)